The Influence of Profitability and Liquidity on Debt Policy (at the Paper Sub-Sector Manufacturing Companies Listed on the IDX 2020-2023) - Norhidayah, Norhidayah; Jaya, Fanlia Prima (Hut Publication Business and Management, 2024)
The purpose of this study is to determine whether profitability and liquidity affect debt policy in paper sub-sector manufacturing companies listed on the IDX in 2020-2023. Profitability is measured by financial ratios, including Return On Asset (ROA), Return On Equity (ROE), Gross Profit Margin (GMP) and Net Profit Margin (NPM). Liquidity is measured by the Current Ratio (CR) and Quick Ratio (QR). Debt policy is measured by the Debt to Equity Ratio (DER). The population in this study is all paper sub-sector companies listed on the IDX in 2020-2023. The sample of this study was taken based on the Purposive sampling technique with a total sample of 3 companies with 48 data. This study uses multiple linear regression analysis methods with SPSS (Statistical Product and Service Solutions) tools. The results of this study indicate that profitability has a significant effect on debt policy. Liquidity has a significant effect on debt policy. Profitability and Liquidity simultaneously have a significant effect on debt policy.